Introduction to psycholinguistics : understanding language science - Traxler, Matthew J. (John Wiley & Sons Ltd., 2023)
"First, let me thank those of you who took the time to read and comment on the last book. I appreciate the effort and have done my level best to keep your thoughts in mind as I went about composing the current edition. Many of the comments were very positive, and even the critical ones had nuggets worth pondering. Like this one from the philosopher Kirkegaard - Overall, an interesting introduction. Some chapters were much more interesting to me than others, which were somewhere between kinda boring and boring. Point taken and I've done what I can to spice things up. (But, hey, you have to be a special kind of person to fall in love with stuff like long-distance dependencies. I'm talking to you, Martin.) Next, let me take a moment to talk about the motivation for writing this book. I've been a college educator (one who teaches at a college; not one who teaches colleges) for over 30 years now (my, how time flies). I have been on the faculty in the Department of Psychology at the University of California, Davis for exactly 20 years today. My research program focuses on neurophysiology and behavior as ways of learning about language comprehension and reading. Language supplies the core means by which humans communicate, form social bonds, and learn from one another. Students of the human condition should have a sound understanding of how languages work and how human cognitive and neural systems are organized to support production and comprehension. My chief goal in writing this book was to provide students with a firm foundation in the fundamentals of language science, as well as some more special and advanced material for those who wish to do a deeper dive. Another major goal was to provide instructors with material that they could use to organize a coherent experience in the classroom. Because language research involves many different players from many different disciplines, and because the field is so vibrant, and because so many language scientists have dedicated themselves to asking and answering deep questions about language, we have a wealth of ideas and findings to explore. It goes without saying that I had to omit many worthy topics and perspectives, but I hope what remains does justice to a lively and important field and the people who generated the knowledge. I admire all of you and am honored to know many of you personally"--